2011
DOI: 10.1007/s12016-011-8267-x
|View full text |Cite
|
Sign up to set email alerts
|

Cutting-Edge Issues in Autoimmune Uveitis

Abstract: Autoimmune uveitis (AIU) is among the leading causes of preventable blindness. It can be isolated, precede, or appear in the course of a systemic autoimmune inflammatory disease. When suspected, AIU should be promptly referred to an ophthalmologist for proper anatomic classification and local treatment. In recurrent and chronic forms, systemic treatment should be started, usually with corticosteroids and immunesuppressors. In cases of lack of efficacy or intolerance, biologic agents such as monoclonal antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 60 publications
0
13
0
2
Order By: Relevance
“…Non-infectious uveitis may occur as an ocular manifestation of a systemic autoimmune condition such as Behçet's disease, sarcoidosis, multiple sclerosis or Vogt-Koyanagi-Harada disease (VKH). 13,14 A study from the Netherlands including almost 400 patients with posterior uveitis, intermediate uveitis or panuveitis reported that around half of all cases were likely to be related to systemic disease. 15 In the remaining cases, no systemic association could be found; these cases are known as idiopathic uveitis, although it is presumed that the disease is still likely to be autoimmune in nature.…”
Section: Aetiology Pathology and Prognosismentioning
confidence: 99%
See 2 more Smart Citations
“…Non-infectious uveitis may occur as an ocular manifestation of a systemic autoimmune condition such as Behçet's disease, sarcoidosis, multiple sclerosis or Vogt-Koyanagi-Harada disease (VKH). 13,14 A study from the Netherlands including almost 400 patients with posterior uveitis, intermediate uveitis or panuveitis reported that around half of all cases were likely to be related to systemic disease. 15 In the remaining cases, no systemic association could be found; these cases are known as idiopathic uveitis, although it is presumed that the disease is still likely to be autoimmune in nature.…”
Section: Aetiology Pathology and Prognosismentioning
confidence: 99%
“…However, pain and redness in the eye, sensitivity to light, loss of peripheral vision and headaches may also be reported. 13 In general, clinical manifestations of uveitis of different aetiologies may be similar but treatment strategies are predominantly determined by the underlying pathophysiology 3 and may often require a multidisciplinary approach.…”
Section: Aetiology Pathology and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…Традиционно предполагается, что неинфекцион-ные увеиты по своей природе являются аутоиммун-ными заболеваниями, возникающими вследствие потери иммунной толерантности к аутоантиге-нам и последующей активации аутореактивных T-лимфоцитов [15,55,57,68,96]. Эта точка зрения сформировалась в результате анализа исследова-ний, проведенных на экспериментальных моделях аутоиммунного увеита, ассоциированного с энце-фалитом, а также вызванного введением эндотокси-на, меланина [64].…”
Section: патофизиолог ические основы исс ле дованияunclassified
“…2 [15]. Неинфекционный увеит считается обусловленным вовлечением в патологический про-цесс Т-клеточного звена иммунитета с участием CD4 + T-хелперных клеток типов 1 и 17, продуциру-ющих соответственно интерферон-гамма и интер-лейкин-17 [15,57,68].…”
Section: патофизиолог ические основы исс ле дованияunclassified